2021
DOI: 10.3390/jcm10102105
|View full text |Cite
|
Sign up to set email alerts
|

Positive Impact of Levothyroxine Treatment on Pregnancy Outcome in Euthyroid Women with Thyroid Autoimmunity Affected by Recurrent Miscarriage

Abstract: Impaired thyroid hormone availability during early pregnancy is associated with recurrent miscarriage (RM) and adverse pregnancy outcomes. The main cause of thyroid dysfunction is thyroid-related autoimmunity (TAI), characterized by a significantly higher serum level of thyroid-stimulating hormone (TSH) compared to that of women without thyroid autoimmunity. TAI is associated with a significantly increased risk of miscarriage, and the incidence of TAI in women experiencing RM is higher compared to normal ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Recent studies suggest that thyroid autoimmunity may adversely impact pregnancy outcomes ( 22 , 23 ). Although the adverse effects of antithyroid antibodies have been well studied in hypothyroid pregnant women, their effects in euthyroid women and in women with SCl hypoT are not well evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggest that thyroid autoimmunity may adversely impact pregnancy outcomes ( 22 , 23 ). Although the adverse effects of antithyroid antibodies have been well studied in hypothyroid pregnant women, their effects in euthyroid women and in women with SCl hypoT are not well evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently demonstrated that TH regulates protease expression and activation of Notch signaling in implantation and embryo development [ 70 ]. Moreover, levothyroxine (LT4) treatment has a positive effect on conception capacity and reduces miscarriages when administered to euthyroid women with autoimmune thyroid disease affected by recurrent miscarriages [ 71 ].…”
Section: Pathophysiology Of the Placenta In Pregnancy Complications And Art Pregnanciesmentioning
confidence: 99%
“…[6][7][8][9][10] Regarding thyroid autoantibodies, such as thyroid peroxidase antibody (TPO-Ab) and thy-roglobulin antibody (Tg-Ab), most available research indicates that the high serum level of these antibodies is associated with the increased rate of recurrent abortions and preterm birth. [11][12][13] At the same time, the prevalence of gestational subclinical hyperthyroidism is around 1.7% and usually not associated with any significant adverse pregnancy outcomes. 14 Profound maternal thyroid physiological changes occur during pregnancy.…”
Section: Introductionmentioning
confidence: 99%